PENGARUH LATIHAN LARI NAIK TURUN TANGGA TERHADAP DAYA TAHAN PESILAT DI PERGURUAN PERSINAS ASAD PONDOK PESANTREN LUHUR MIFTAHUL HUDA PEKANBARU - Refandi Mohamat Y.K; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is the weak endurance of fighters at persinas ASAD college Pondok Pesantren Luhur Miftahul Huda Pekanbaru. The title of this research is "The Influence of Running Exercises Up and Down the Stairs On The Endurance of Fighters At Persinas ASAD College Pondok Pesantren Luhur Miftahul Huda Pekanbaru". So that the future goal of the Fighters can show even better performances during training and martial arts matches. This form of research is (one group pretest-postest design) with the population of Fighters In Persinas ASAD College Pondok Pesantren Luhur Miftahul Huda Pekanbaru. The data in this study is the entire population of 8 people. The instruments carried out in this study were using the Multi-stage Running test, which aims to find out how the fighter's endurance influences. To test normality use lilifours test at a significant level of 0.05α. Based on normality test analysis X data produces Lcount of 0.166 and Ltabel 0.285, meaning Lcount < Ltable. while variable Y produces A-count of 0.1883 and Ltable of 0.285. This means Lcount < LTabel. thus the data is distributed normally. Thus it can be concluded that for the influence between variable x and variable y obtained value t = 6.45 then Lcount > Ltablel that is (8,538) > (1,895), then Ha received, in other words there is a significant influence on the influence of running exercises up and down the stairs against the durability of fighters in the College Persinas ASAD Pondok Pesantren Luhur Miftahul Huda Pekanbaru.Key Words: Up and Down The Stairs Running Exercises, Endurance